Spasmodic Torticollis—A Multicentre Study on Behavioural Aspects II: Signs, Symptoms and Course - F. Heinen; C. E. Scheidt; T. Nickel; O. Rayki; J. Wissel; W. Poewe; R. Benecke; G. Arnold; W. Oertel; R. Dengler; G. Deuschl (Behavioural Neurology)
This paper deals with signs, symptoms and course in spasmodic torticollis (ST). Two hundred and fifty-six patients were included in the study, 59.3% women, 40.7% men. The mean age was 49.1 years. Rotating torticollis out-numbered latero- and antero-retrocollis. A family history of ST occurred in 3.1% of the total sample. First degree relatives were affected in 2.3%. Thirty-four per cent of the patients had additional dystonic symptoms. Most frequently these affected the upper extremities (13%), and less often the legs. Of the patients 19.1% had experienced a period of complete remission. The correlations between the severity of the signs and the neurological symptoms are surprisingly weak.